A hybrid optimization technique for solving economic emission load dispatch problem - Roslan N.; Khader P.S.A.; Nordin A.; Jaafar S. (World Academy of Research in Science and Engineering, 2023)
This paper presents the application of a hybrid optimization technique termed as Immune-Evolutionary Programming (IEP) to solve Economic Emission Load Dispatch (EELD) of power system. IEP has been tested on the IEEE 30-Bus Reliability Test System (RTS) with two case studies: base case and loaded case. The objective of the optimization process is to minimize the total emission. Total system loss and total generation cost are calculated and observed while minimizing the emission. It is found that IEP is suitable to be used to solve EELD problemin giving better total emission, total system loss and total generation cost compared to the pre-optimization results for the both base case and loaded case. 2020, World Academy of Research in Science and Engineering. All rights reserved.